Whither Democratic Legitimism?: Contextualizing Recent Developments in the Recognition and Non-recognition of Governments. (2014) - R. Roth, Brad
Abstract : Erika de Wet has provided a useful and balanced assessment of the current state of the international law of governmental illegitimacy. Her account quite rightly concludes that "democratic legitimacy is not yet a requirement for the recognition of a de jure government under customary international law." What follows below seeks to expand on her observations in two ways: by developing somewhat further the doctrinal linkages to which she alludes; and by explaining the failure of a consistently legitimist state practice to materialize, in light of the dynamics of the legal order within which the question of governmental illegitimacy is embedded.